A importância dos mecanismos comportamentais de resistência para a dinâmica populacional de abelhas Apis mellifera e o parasita Varroa destructor - Santos, Joyce de Figueiró (2014)
The ectoparasitic mite Varroa destructor that parasitize honey bees has become a global problem. Although this mite is unlikely to, by itself, cause the mortality of hives, it plays an important role as a vector for many viral diseases. These diseases are identified as some of the most important reasons for the Colony Collapse Disorder. The effects of V.destructor infestation are disparate in different parts of the world. Greater morbidity - in the form of colony losses - has been reported in colonies of European honey bees (EHB) in countries of Europe, Asia and North America. However, this mite has been in Brasil for many years and there are no reports of losses of Africanized honey bees (AHB) colonies. Studies carried out in Mexico showed that some resistance behaviors to the Varroa mite - especially grooming and hygienic behavior - appear to be different in each subspecies. Could those mechanisms explain why the AHB are less susceptible to Colony Collapse Disorder? In order to answer this question, we propose a mathematical model based on differential equations, to analyze the role of these resistance mechanisms in the overall health of the colony, and it’s ability to face environmental challenges.